If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -73 = 6x + 77 Reorder the terms: -73 + 11x = 6x + 77 Reorder the terms: -73 + 11x = 77 + 6x Solving -73 + 11x = 77 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -73 + 11x + -6x = 77 + 6x + -6x Combine like terms: 11x + -6x = 5x -73 + 5x = 77 + 6x + -6x Combine like terms: 6x + -6x = 0 -73 + 5x = 77 + 0 -73 + 5x = 77 Add '73' to each side of the equation. -73 + 73 + 5x = 77 + 73 Combine like terms: -73 + 73 = 0 0 + 5x = 77 + 73 5x = 77 + 73 Combine like terms: 77 + 73 = 150 5x = 150 Divide each side by '5'. x = 30 Simplifying x = 30
| 10x-5-7x=29 | | -30-3x=6y | | 75=6w | | 2x+-2=16 | | y+1=3(-7-2) | | 3b^2+40=-19b | | 5z-3z=z-16 | | -8-3y=-3x | | -x^2+4=3x-1x^2 | | 6(u-2)+2(u-53)=2 | | 0+1=3(x-2) | | -4y+16=-2x | | .2a=48 | | 6(a-7)+6=3(a-6) | | -2.2(n-.5)=-1.1(n-1.5) | | 4x^2+5=2x-1 | | 4*3-6*8+(-25)= | | 5x-5=2x+34 | | 3x=5y+5 | | 4+6x=18-(2-2x) | | 3b^2-40=-196 | | X+1+7=4 | | -5x+(-4-9)=6 | | -5p=2p-35 | | 2(6-x)=2 | | -14+x=-32 | | (x-6y)(5x+6y)=0 | | 3y+x=0 | | (8x-3)-(4x-8)= | | 5x-25=2(2x+3) | | -3-3y=-15x | | y+1=3(0-2) |